2014
DOI: 10.1039/c4ob01863j
|View full text |Cite
|
Sign up to set email alerts
|

Total syntheses of cis-cyclopropane fatty acids: dihydromalvalic acid, dihydrosterculic acid, lactobacillic acid, and 9,10-methylenehexadecanoic acid

Abstract: cis-Cyclopropane fatty acids (cis-CFAs) are widespread constituents of the seed oils of subtropical plants, membrane components of bacteria and protozoa, and the fats and phospholipids of animals. We describe a systematic approach to the synthesis of enantiomeric pairs of four cis-CFAs: cis-9,10-methylenehexadecanoic acid, lactobacillic acid, dihydromalvalic acid, and dihydrosterculic acid. The approach commences with Rh2(OAc)4-catalyzed cyclopropenation of 1-octyne and 1-decyne, and hinges on the preparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 51 publications
3
23
0
Order By: Relevance
“…The compounds identified under LC-MS in this study were mostly non-volatile and could not have been identified by GC-MS. The novel fatty acid is quite interesting and cyclopropane fatty acids (CFA) have been isolated from several sources such as millipedes (Oudejans, 1971), molluscs (Fenical et al, 1979), molds (Saito and Ochiai, 1998) and a lot of them have been synthesized (Shah et al, 2014, Arai et al, 1983. CFAs are typically found in microorganisms, seed oils of subtropical plants, protozoa and less commonly, within fats and phospholipids produced by animals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds identified under LC-MS in this study were mostly non-volatile and could not have been identified by GC-MS. The novel fatty acid is quite interesting and cyclopropane fatty acids (CFA) have been isolated from several sources such as millipedes (Oudejans, 1971), molluscs (Fenical et al, 1979), molds (Saito and Ochiai, 1998) and a lot of them have been synthesized (Shah et al, 2014, Arai et al, 1983. CFAs are typically found in microorganisms, seed oils of subtropical plants, protozoa and less commonly, within fats and phospholipids produced by animals.…”
Section: Resultsmentioning
confidence: 99%
“…CFAs are typically found in microorganisms, seed oils of subtropical plants, protozoa and less commonly, within fats and phospholipids produced by animals. They are biosynthesized by methylenation of cis-unsaturated fatty acids via esterification to phospholipids with S-adenosylmethionine and catalyzed by CFA synthases (Shah et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Like β-gentiobiosyl diglycerides, α-glucosyl diacylglycerides are also lipid anchors of lipoteichoic acid, which do not signal through Mincle. Williams and co-workers synthesized an α-glucosyl diglyceride from the commensal bacterium Lactobacillus plantarum ( 61 ), which contained a CP fatty acid (dihydrosterculic acid) and oleic acid and demonstrated that this could activate human and mouse Mincle NFAT-GFP reporter cells, with similar potency ( 62 , 63 ). A range of analogs were prepared that lacked cyclopropanation and/or unsaturation; all signaled though human and mouse Mincle with similar potency.…”
Section: Sensing Of Microbial Lipids From Pathogens and Commensalsmentioning
confidence: 99%
“…Under the optimized conditions, EDA/erucate molar ratio ¼ 3, EDA slowly added during 10 h, 1 mol% Cu(OTf) 2 , CH 2 Cl 2 as solvent, room temperature, 15 h total reaction time, total conversion of methyl erucate to the trans-5 and cis-6 cyclopropanes was obtained, with a trans/cis selectivity of 69/31. Both diastereomers were separated and characterized by mass spectrometry and NMR using CDCl 3 and bezene-d 6 as solvents (see ESI †). c Determined by gas chromatography.…”
Section: 28mentioning
confidence: 99%
“…3 Cyclopropane fatty acids are present in nature, 4 and their synthesis has been usually tackled by construction of the alkyl chains from the pre-formed cyclopropane ring. 5,6 The Simmons-Smith reaction has been also described for this purpose, 7 but surprisingly, the catalytic cyclopropanation of carbon-carbon double bonds has been scarcely explored. Only in one case unsaturated fatty esters were made react with diazomethane in a Pd catalyzed cyclopropanation, 8 whereas one single example was described for the copper catalyzed cyclopropanation with ethyl diazoacetate 9 and another one using diazoketones.…”
Section: Introductionmentioning
confidence: 99%